Deteksi Jamur Malassezia spp. Penyebab Infeksi Jamur Kulit Pada Santri Pondok Pesantren Kota Denpasar - Prasetya, Didik; Abadi, Moh Fairuz (poltekkes kemenkes pontianak, 2024)
Islamic boarding schools are educational or non-formal educational institutions to learn more about religion. Boarding school is a place that has the potential to affect skin health. Skin infection is one of the diseases often suffered by students. One of them is a skin infection caused by fungi or better known as Tinea versicolor or tinea versicolor. Factors that can affect skin health include physical factors, chemical factors, and biological factors. This study aims to identify Malassezia spp fungi in the skin scrapings of students and determine the percentage or prevalence of Malassezia spp. fungi causing skin fungal infections in students at Hidayatullah Islamic Boarding School in Denpasar City. This type of research is descriptive with a population of all high school student council members, 17 male students and 23 female students with a total of 40 students. The results obtained from the examination were that there was 1 sample from male students who were positive for Malassezia spp. which causes Pityriasis versicolor or also called panu. Skin diseases can infect easily if you do not maintain personal hygiene.